Characterizing the resistome of Escherichia coli isolated from farmed white-tailed deer (Odocoileus virginianus) in Florida, United States - Surphlis, Austin C.; Cheng, An-Chi; Metrailer, Morgan C.; Bluhm, Andrew P.; Jiranantasak, Treenate; Tuozzo, Frank; Doster, Enrique; Blackburn, Jason K.; Jeong, Kwangcheol C.; Boucher, Christina; Campos-Krauer, Juan M.; Wisely, Samantha M.; et al. (Frontiers in Microbiology, 2025)
BackgroundAntimicrobial resistance (AMR) is a critical public health issue; with many experts suggesting we are already in a post-antibiotic era. The widespread use of antibiotics in agriculture, human, and veterinary medicine influences the spread of antibiotic resistance genes (ARGs) among humans, animals, and the environment. In Florida, white-tailed deer (WTD; Odocoileus virginianus) farming plays a vital role in the economy and environment, but the use of antimicrobials in farmed WTD, along with their proximity to urban and agricultural areas, increases the pressure for AMR development. Understanding the resistance patterns in these deer populations is crucial for their health, as well as for wildlife and ecosystems. This research aimed to investigate the resistome of Florida-farmed WTD. Escherichia coli, a commonly used indicator bacterium, was chosen to study AMR due to its pathogenicity and ease of culture.MethodsSamples from various tissues were collected during necropsy. Escherichia coli was isolated and cultured, and whole-genome sequencing was performed using a high-throughput NovaSeq platform. The AMR++ v 3.0 pipeline and ResistoXplorer tool were employed for data normalization and analysis. Antimicrobial susceptibility testing of the E. coli isolates was conducted using the Kirby-Bauer disk diffusion method on Mueller-Hinton agar, based on the guidelines and recommendations in the CLSI VET01S.ResultsA total of 362 unique ARGs were identified, conferring resistance to 12 antimicrobial classes via 19 mechanisms. The most abundant classes were ß-lactams, multi-drug resistance, and bacitracin. Antimicrobial susceptibility testing showed that 30% of E. coli isolates were resistant to at least one drug under aerobic conditions, while 68% were resistant under anaerobic conditions. Moreover, 15% of isolates displayed multi-drug resistance in both conditions. The study also compared genotypic and phenotypic AMR profiles using kappa, revealing good to very good agreement for several drugs.ConclusionThis is the first study to characterize the resistome of farmed WTD in Florida, providing valuable data for better management of antimicrobial use in these populations.